The Influence Of Compensation, Work Motivation, and Work Discipline On Employee Performance at PT. Heulang Bandung - Rennie Rennie; Sri Sundari; Fernandez Hutagalung; Marisi Pakpahan; Irwan Tanamas (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
Introduction: Human resources play a crucial role in the sustainability of a company, and good employee performance is a critical aspect of its operations. It is important for companies to understand and improve the factors influencing employee performance to enhance the overall quality of the organization. Objective: This study aims to analyse the influence of compensation, work motivation, and work discipline on employee performance at PT. Heulang Bandung, both partially and simultaneously. Method: The research was conducted on the employees of PT. Heulang Bandung, which has a total of 115 employees, using a sample of 55 employees and employing a quantitative method to analyse the influence of variable X on Y. Results: The findings indicate that compensation has a negative and insignificant effect on employee performance (regression coefficient -0.051), while work motivation (coefficient 0.465) and work discipline (coefficient 0.749) have positive and significant effects. These three variables collectively influence employee performance by 86.1%, with 13.9% affected by other factors. The F-test shows a significant effect of these three variables on employee performance with a significance value of 0.000. Conclusion: Work motivation and discipline are the main factors influencing employee performance at PT. Heulang Bandung, while compensation has a lesser impact.